Communicating Arctic-midlatitude weather and ecosystem connections: direct observations and sources of intermittency - James E Overland; Baek-Min Kim; Yoshihiro Tachibana (Environmental Research Letters, 2021)
There is controversy over the extent that Arctic change can influence midlatitude extreme weather and vis-versa. Part of the uncertainty is due to the intermittency of the connection through the jet stream and polar vortex that leads to different emphases when communicating research. Although statistical studies and model results often show weak or non-existent connections, we can provide two observational examples. Three interactive physical processes are involved through atmospheric dynamics: (a) internal atmospheric jet stream/polar vortex processes that add to the persistence of a wavy jet stream; (b) warm and humid air transport into an existing longwave atmospheric pattern; and (c) local thermodynamic surface forcing, often associated with loss of sea ice. All three atmospheric processes were active in two recent studies: winter 2016 in the Barents Sea and winter 2018 in the Bering/Chukchi Sea. Both impacted sea ice loss and the entire marine ecosystem food chain, and resulted in downstream cold air transport into midlatitudes. Societal anticipation is necessary to respond to a repeat of such events. Both the North American and eastern Asia examples show a causal connection from atmospheric and ocean physics through ecosystem disruption to human impacts. Thus global warming influences can be more than a local heating response, but follow a chain of events involving disruption of the jet stream.